LEARNING THE KEMBHANG RADDIN DANCE IN EXTRACURRICULAR ACTIVITTES OF SMP 2 TENGGARANG BONDOWOSO REGENCY - puspita kasih, maharani; Suryandoko, Welly (Solah, 2025)
This study aims to describe the learning process and method of Kembhang Raddin Dance in extracurricular activities at SMPN 2 Tenggarang, Bondowoso Regency. The Kembhang Raddin Dance is a regional creation dance created by the Bondowoso Regency Cultural Arts MGMP which is full of cultural values and aesthetic expressions. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of dance coaches and 25 students participating in extracurricular activities. The results of the study show that the learning process takes place in three stages, namely dance introduction, technique training, and evaluation. The learning methods used include demonstration methods and drill methods. The demonstration method is effective for building visual understanding of movement, while the drill method strengthens motor skills through repetitive exercise. These two methods are able to improve mastery of dance techniques, build student confidence, and foster discipline and cooperation. In addition, these activities contribute to the preservation of local culture through art education in schools. Thus, the application of the right learning methods can support the achievement of dance learning goals optimally in extracurricular activities.